Transcending the illusion of separateness : a grounded theory study of processes that occur between client and horse during Equine Facilitated Learning : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Albany, Aotearoa New Zealand - Stanford, Sophie (Massey University, 2024)
Equine Facilitated Learning (EFL) has been reported as a promising growth and well-being practice, with the potential to benefit humans in a variety of ways. However, explanation of relevant theoretical foundations is currently lacking. Aiming to contribute to the theoretical base of this practice, this research employs grounded theory methods to explore processes that occur between client and horse during EFL. Client voices are centred via their role as participants of this study. Their perspectives form the dataset that highlights experiencing connection as the core category. The findings outline two processes: the relationship building process and the personalising process, which sit within the wider EFL context. Ultimately, the findings are abstracted to a tentative grounded theory that explains the processes occurring between client and horse as complex and dynamic systems of reciprocal influence. This is discussed in relation to current literature and practical implications, to highlight how this study extends available understandings of EFL. Limitations of the research are also noted, as well as future recommendations.
Keywords: Equine Facilitated Learning, EFL, Equine Assisted Learning, EAL, animal assisted therapy, animal assisted interventions, grounded theory, informed grounded theory, theory development, complex processes, clinical psychology, well-being, learning, qualitative research; 520304 Health psychology